MANIPULATIVES USE IN MATHEMATICS CLASSROOMS OF INCLUSIVE BASIC SCHOOLS IN GHANA - Adu, Augustina; Apawu, Jones; Obeng-Denteh, William (Physical and Mathematical Education, 2025)
Formulation of the problem. Mathematics is essential in every individual’s life, including that of Learners with Visual Impairment (LVI), as it helps them acquire the competencies required in their daily life and profession. There is a growing emphasis on inclusive basic schools to avoid discrimination among people with disability, Such as Learners with Visual Impairment (LVI). One subject that LVI finds difficult to understand is mathematics because it utilizes many graphics that are challenging for LVI to comprehend. Manipulative materials help reduce the abstract nature of mathematical concepts by making them more visible to learners, including those with learning difficulties. Despite the benefits of manipulatives in inclusive primary classrooms, there is a lack of research on how manipulatives are used in inclusive primary schools in Ghana to enhance learners’ understanding of mathematical concepts. Guided by cognitive and social constructivism theory, this study explores how basic school mathematics teachers make manipulatives accessible to Learners with Visual Impairment (LVI), the support they provide, the assessment strategies they use, and the difficulties they encounter when using manipulatives to teach mathematics to LVI. Materials and methods. This study employed a case study research design. Six inclusive basic mathematics teachers were interviewed, and the results were analysed thematically. Results. Findings from the study indicated that most teachers do not have manipulatives in their schools and do not employ them during mathematics instruction. The results also showed that, since most teachers do not use manipulatives in teaching mathematical concepts, they were unable to identify the challenges they face when teaching LVI mathematical concepts with manipulatives. Conclusions. Based on the outcome of this study, manipulatives for teaching mathematics, especially to LIVs, should be made available in inclusive basic schools in Ghana. Teachers in inclusive basic schools in Ghana should be given workshops and seminars on the use of manipulatives in teaching mathematics to LVI.